Suicide and adolescence in the actual debate - Di Pietro, Maria Luisa; Lucattini, Adelia (Medicina e Morale, 1994)
The authors intend to give an answer to three questions: 1. Why would an adolescent commit suicide?; 2. the reasons of such an action; 3. the prevention of the suicide. After a brief review about suicide's behaviour, the article deals with the problem of the suicide in adolescent age, regarding epidemiology and means to attempting the suicide. With regard to etiology of the suicide, the authors note that such an action is apparently characterized by surprise and incomprehensibility. Really, the suicide must be considered as final and manifest act of an intricate plot of processes, dreams, desires and experiences determined by both adolescent's mental reality and external human relations of lhe social environment. Therefore, it's difficult to consider the "trigger factors" of the suicide and the authors prefer the term "risk factors". They are: adolescent's vulnerable personality; the presence of menta! disorders, especially depression; adolescent's conflictual relation with own body; alcoholism and drug addiction; family situation (unsolved conflicts or presence in the family of mental disorders or suicides); mass media, that can strenghten the adolescent's vulnerability; school failures; "difficult" social environment; suicide adolescent's fancies. The authors determine three levels of suicide adolescent's prevention: primary, by means addressed to population at risk; secondary, to avoid relapse; tertiary, by control of injuries caused by suicide behaviour. The article ends up with a "life education" proposition that takes into account the three human dimensions: self, others, trascendence.